INCREASE OF BREEDING AND DEATH IN THE BEE FAMILY, BENEFIT PERIODS - Jamolov Rapikjon; Sharofiddinova Gulirano (Journals Park Publishing, 2024)
In the article, there were many attempts to study the spring and summer development periods of the bee family in the climatic conditions of Uzbekistan. In the conducted studies, it was recognized that there are 3 specific periods in the development of the bee family in the conditions of our republic.
Keywords: Bee family, spring and summer, productive, nectar, periods, different species, village, egg, swarm, brood, colony, valley, queen bee, worker bee, male bee, temperature, relative humidity.